Origin of the giant persistent photoconductivity in LaAlO3/SrTiO3 heterostructures probed by noise spectroscopy - Eom, Kitae; Lee, Jung Woo; Yang, Gyeongmo; Kim, Youngmin; Jeon, Jaeyoung; Yeon, Jieun; Lee, Hyungwoo (Journal of Materials Science and Technology, 2023)
LaAlO3/SrTiO3 (LAO/STO) heterostructures have shown a strong persistent photoconductivity (PPC) at room temperature. The abnormally strong PPC has attracted immense research interest due to its possible applications in optically-tunable electronic devices. Despite its promise, the fundamental understanding of the PPC in the LAO/STO heterostructures is still elusive. Herein, we report that the giant PPC originates from the photo-induced valence change in oxygen vacancies near the LAO/STO interface. Our spectral analysis of the photocurrent and the model-fitting study consistently show that the ionized oxygen vacancies near the interface are neutralized during the electron relaxation process. They hinder the complete relaxation of the photoexcited electrons by the deeply-located oxygen vacancies and result in the strong PPC. The change in the ionization state distribution of the oxygen vacancies is probed by the persistent noise behavior at the frequency between 1 kHz and 20 kHz regime. These results provide insight into the role of oxygen vacancies in influencing the internal charge distribution and triggering the PPC phenomena in complex oxide heterostructures.
Keywords: LaAlO 3; LaAlO3/SrTiO3 heterostructure; Low-Frequency Noise; Noise spectroscopy; Persistent Photoconductivity; Research interests; Spectral analyze; SrTiO 3; Tunables; Two-dimensional electron gas; LaAlO3/SrTiO3 heterostructures; Low-frequency noise; Oxygen vacancies; Persistent photoconductivity; Spectral analyses; Two-dimensional electron gases